Antibiotic-resistant soil bacteria in high-altitude (5000–6000 m) soils of the Himalaya - Blaž STRES (Acta Agriculturae Slovenica, 2010)
In this study, low-carbon soils collected from an altitude transect from 5000 m to 6000 m were adopted as a simple model system with lower interaction complexity. This could help disentangle the basic environmental factors shaping the abundance and distribution of expressed resistance traits in culturable portion of fast growing heterotrophic strains. Improved plate counts were performed at 4 °C using 0.01 diluted nutrient broth supplemented with cold soil extract as a general media and additionally supplemented with antibiotics Ampicillin, Erythromycin, Kanamycin and Tetracyclin. A number of colonies (500) isolated from six locations were also tested separately for their antibiotic resistance. The results show that these high-altitude cold soils contained bacterial populations culturable at 4 °C in the range of 106 cells / g that were resistant to the four antibiotics and their various combinations tested in this study. The highest prevalence of resistance was observed in vegetated soils, whereas almost two orders of magnitude lower abundance of resistant cells was cultured from barren soils. Redundancy analysis showed that vegetation, soil carbon and pH were successful in explaining the interaction between environmental parameters and various culturable fractions of cold soil bacteria used in this study.